The Euro Area in Between Crises? Considerations on Fiscal Policies and Rules - Cristina Checherita-Westphal; Sebastian Hauptmeier; Nadine Leiner-Killinger (Intereconomics)
Abstract Credibility of the revised fiscal rules will be crucial so that vulnerable countries can benefit from confidence effects. National ownership will be key in that respect and can be supported via a stronger role of independent national fiscal institutions.